(untitled) - Cartwright, Kent (Cambridge, 1999)
English drama at the beginning of the sixteenth century was allegorical, didactic and moralistic; but by the end of the century theater was censured as emotional and even immoral. How could such a change occur? Kent Cartwright suggests that some theories of early Renaissance theater need to be reconsidered. He proposes that humanist drama of the sixteenth century is theatrically exciting and socially significant, and he attempts to integrate popular and humanist values rather than setting them against each other.
Keywords: Renaissance,English drama,Kịch Anh Quốc,Phục hưng,Theater,Nhà hát; History and criticism,Lịch sử và phê bình,History,Lịch sử; 16th century,16th century,Thế kỷ 16; England,Thế kỷ 16,Anh quốc,England,Anh quốc